Komunikasi Interpersonal dan Representasi Emosi dalam Film Avengers: Endgame (2019): Studi Kasus Dinamika Tokoh dan Implikasi terhadap Wisata Populer - Airumi Qanitah Sari; Shella Fadhilah; Bintang Halim Triasanda; Rava Putra Suyono; Arsih Amalia Chandra Permata; Wiyata Wiyata (Institut Nalanda, 2025)
This research discusses interpersonal communication and emotional representation in the film Avengers: Endgame (2019), focusing on how the dynamics between the main characters shape emotional resonance that influences the audience's tourism behavior. The background of this study departs from the phenomenon of film-induced tourism, where the emotional attachment of the audience to fictional characters and locations triggers the desire to visit the actual filming locations of the film. The aim of the research is to identify forms of interpersonal communication in films and to examine their implications for tourist interest in filming locations. With a descriptive qualitative approach and the Stimulus–Organism–Response (S–O–R) model analysis, data were collected through scene observation and media documentation. The results show that verbal and nonverbal communication in the form of expressions of loss, empathy, social support, and sacrifice build a strong emotional bond with the audience. This elicits a tangible response in the form of tourist visits to locations such as Stark Cabin and St Abbs. This research concludes that interpersonal communication in films not only strengthens the narrative but also serves as an affective bridge that shapes the image of the destination. These findings have implications for cinema-based tourism promotion strategies and the use of emotional narratives in the creative industry.